The New Cooperative Program ‘KMP’ And The Indonesian Pancasila Economy: A Legal And Philosophical Approach - Koswara, Asep (Universitas Duta Bangsa Surakarta, 2025)
The new emergence of Koperasi Merah Putih (KMP) reflects Indonesia’s renewed effort to realign its economic development with the foundational values of Pancasila. Despite the country’s rich history of cooperative movements, legal fragmentation and philosophical detachment have hindered their transformative potential. This paper aims to analyze KMP as both a legal and philosophical manifestation of Indonesia’s economic identity. Using a descriptive qualitative approach, the study examines existing legal frameworks, the integration of Pancasila values into cooperative practice, and the institutional dynamics surrounding KMP implementation. Key findings show that while KMP has a strong normative foundation rooted in Law No. 25/1992 and the 1945 Constitution, its practical application faces challenges in regulatory adaptation, institutional synergy, and philosophical consistency. The research highlights the importance of reconstructing legal instruments to support village-based economic democracy and advocates for embedding justice, solidarity, and identity within the cooperative structure. This study concludes that KMP can serve as a strategic model for reimagining Indonesia’s future economy—one that is community-centered, ethically grounded, and constitutionally aligned.